2022
DOI: 10.1108/ajems-06-2021-0281
|View full text |Cite
|
Sign up to set email alerts
|

Government domestic debt arrears and private investment in Sub-Saharan Africa

Abstract: PurposeThis study investigates the effect of government domestic payment arrears on private investment. The authors argue that an increase in government domestic arrears can reduce private sector investment owing to the competition for credit.Design/methodology/approachThe prediction is empirically tested using data for 33 Sub-Saharan Africa (SSA) countries for the period 2007–2018 using a panel general methods of moment estimation technique. This is also complemented with impulse responses derived from the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Thus, private investors, to some extent, are convinced of getting positive returns based on the investment climate provided in the previous year. This finding is in line with Anyanwu et al (2018) and Kulu, Brafu‐Insaidoo, Peprah, et al (2022).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, private investors, to some extent, are convinced of getting positive returns based on the investment climate provided in the previous year. This finding is in line with Anyanwu et al (2018) and Kulu, Brafu‐Insaidoo, Peprah, et al (2022).…”
Section: Resultssupporting
confidence: 91%
“…As the engine of economic growth in most sub‐Saharan African (SSA) countries, the activities of the private sector are of much relevance to policy‐makers and leaders (Abor et al, 2019; Guei & Choga, 2022; Kulu, Brafu‐Insaidoo, Peprah, et al, 2022). In providing a complementary role in the economy, the investment made by the private sector in the domestic economy affects important variables in the economy, such as the rate of employment, savings, and gross domestic product (GDP) (Khan & Reinhart, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in rural areas, there is a crowding-in effect. Using the panel data method, Kulu et al (2021) examine the crowding-out effect of government domestic payment arrears on private investment for 33 Sub-Saharan African countries from 2007 to 2018. As a conclusion of the analysis, the authors point out that government domestic payment arrears have a crowdingout effect on private investment.…”
Section: Literaturementioning
confidence: 99%
“…Unlike these studies, the number of studies examining the crowding-out effect of public investments on the private sector is substantial (Argimon et al, 1997;Cil-Yavuz, 2001;Uysal & Mucuk, 2004;Bilgili, 2003;Altunc & Senturk, 2010;Cural et al, 2012;Mahmoudzadeh et al, 2013;Yarasır-Tulumce & Buyrukoglu, 2013;Kesbic et al, 2016;Andrade & Duarte, 2016). However, studies examining the crowdingout effect of the public sector's debt structure on the private sector are relatively new and limited (Demir, 2017;Caskurlu, 2020;Ela & Pata, 2020;Kulu et al, 2021;Penzin & Oladipo, 2021;Vanlear et al, 2021). In short, various econometric methods, data sets, and samples are preferred in empirical studies.…”
Section: Introductionmentioning
confidence: 99%
“…For an increase in the financial stability gap, for instance, we conceptualize it as a decrease in financial stability. In SSA, Kulu et al (2022b) used annual time series data on banks' z-score to estimate the financial stability gap for some countries in SSA and also for some subregional communities such as the Economic Community of West Africa States, Eastern Africa Community (EAC) and the Economic Community of Central Africa States. It was revealed that for the period under study, Kenya, Cote d'Ivoire, Sao Tome Principe, Niger and Zimbabwe recorded the least gaps in financial stability.…”
Section: Literature Reviewmentioning
confidence: 99%